Study on Compatibilization of Recycled Polypropylene/ Polyethylene Terephthalate Blend From Coastal Plastic Waste Using Maleic Anhydride - Mohd Dzulkiflee, Hamzah (2012)
Increase in human activities due to economic growth caused waste generation rate is continuously rising up every year. Due to lack of responsibility and inefficient waste management, plastic waste has become a major source of environmental pollution and in this attempt, marine pollution is one of the serious problem that occur for the past ten years in which plastics are the main waste that always be found. The recycling of heterogeneous plastic waste gives secondary materials with poor properties because of a scarce compatibility among the polymers present in the waste. Compatibilization of heterogeneous blends is thus a primary aim of the research on recycling. Blends of polyolefin are particularly difficult to design due to the different chemical nature of thetwo classes of polymers. In this work the goal is achieved by using a commercial maleicanhydride to compatibilist polypropylene (PP) and polyethylene terephthalate (PET) blend from recycled plastic waste. All sample of PP/PET blends were prepared in an twin screw extruder with thermal profile used for all the extrusions was 195-200-205-205-200-195°Cand the screws speed was 60 rpm. Blends of recycled PP/PET show amorphology with the large voids, due to a limited adhesion between the two phases, anda brittle behaviour with poor mechanical properties. By using small amounts ofcompatibilizer, the blend adhere very well in which degree of dispersion and surfaceadhesion increased and the two phases become almost indistinguishable. in this attempt,addition of 9% by mass of maleic anhydride shows the best morphological properties.TGA study shows that there is no big change in thermal degradation means thatcompatibilizer does not reduce thermal resistance of the blend. Some mechanicalproperties are also considerably improved. Tensile strength for addition of 9% by massof maleic anhydride gives the highest tensile strength in which it surpass tensile strengthof homogenous PP and much more closer to virgin PP. Morphology study explainingthat why addition of 9% of MA gives the highest tensile strength in comparison to the other samples. It can be concluded that interfacial activity does not require large amountof compatibilizer and it only needed to present in optimum amount in which a few percents would be sufficient to improve the morphology and mechanical properties of the polymeric blends.